POLICIES AND REFORMS OF ROZA OTUNBAYEVA (Modern education and development, 2025)
This paper explores the political policies and reforms implemented by Roza Otunbayeva during her tenure as the interim President of the Kyrgyz Republic from 2010 to 2011. Her leadership was crucial in transitioning Kyrgyzstan from an authoritarian regime to a parliamentary democracy. The study highlights her efforts in constitutional reform, human rights protection, judicial independence, and anti-corruption measures. Furthermore, the paper analyzes the significance of her contributions to civil society development and the stabilization of post-conflict regions. Otunbayeva’s presidency is considered a turning point in Kyrgyzstan’s democratic evolution and offers a unique case of female leadership in Central Asia.